2023
DOI: 10.3389/fcvm.2023.1272945
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the boundaries of innovation: the potential of ex vivo organ perfusion from an interdisciplinary point of view

Jasper Iske,
Andreas Schroeter,
Samuel Knoedler
et al.

Abstract: Ex vivo machine perfusion (EVMP) is an emerging technique for preserving explanted solid organs with primary application in allogeneic organ transplantation. EVMP has been established as an alternative to the standard of care static-cold preservation, allowing for prolonged preservation and real-time monitoring of organ quality while reducing/preventing ischemia–reperfusion injury. Moreover, it has paved the way to involve expanded criteria donors, e.g., after circulatory death, thus expanding the donor organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 211 publications
0
2
0
Order By: Relevance
“…This study aimed to evaluate the feasibility of the VP.S ENCORE® device to preserve human donor-derived hearts not utilized for transplant for prolonged time. Study results revealed that hypothermic machine perfusion (HMP) between 4 and 10°C contributes to the reduction of the active metabolic state in cardiac grafts, as measured by low lactate and other myocardial markers expression, thereby minimizing the risk of the accumulation of toxic metabolites while maintaining cardiac viability ( 26 ). Examination of various metabolic markers, including oxygen consumption and lactate levels, demonstrated notable correlations with myocardial function during machine perfusion ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to evaluate the feasibility of the VP.S ENCORE® device to preserve human donor-derived hearts not utilized for transplant for prolonged time. Study results revealed that hypothermic machine perfusion (HMP) between 4 and 10°C contributes to the reduction of the active metabolic state in cardiac grafts, as measured by low lactate and other myocardial markers expression, thereby minimizing the risk of the accumulation of toxic metabolites while maintaining cardiac viability ( 26 ). Examination of various metabolic markers, including oxygen consumption and lactate levels, demonstrated notable correlations with myocardial function during machine perfusion ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…For their application in transplantation, the most efficacious deployment of senolytics needs to be evaluated. Hereby, treatment of the donor, the recipient, and the organ itself by recruiting ex vivo perfusion systems ( 24 , 25 ) need to be compared to ensure most efficient treatment while sparing side effects.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Studies are still ongoing to determine and/or improve the optimal perfusion solution and its gaseous composition, system temperature, flow conditions, etc. Currently, perfusate contains several pharmacologic components to maintain vascular homeostasis and is heparinized to avoid thrombosis of the system [43].…”
Section: Ischemia-reperfusion Injury and Thrombo-inflammation In The ...mentioning
confidence: 99%